PROMOSI DIGITAL OBJEK CAGAR BUDAYA ISTANA RAJA ROKAN DI KECAMATAN ROKAN IV KOTO KABUPATEN ROKAN HULU - Adhitia, Resty; Sulistyani, Andri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
Rokan IV Koto District is one of the districts in Rokan Hulu Regency which is quite well-known because it has several tourist attractions that have the potential to become destinations, especially for the people of Rokan Hulu Regency. One of the destinations in Rokan IV Koto District is the King Rokan Palace, precisely in Koto Ruang Village. The King Rokan Palace is one of the cultural heritage tourist attractions that has great potential to be developed as a leading tourist destination in Rokan Hulu Regency. However, the Digital Promotion of this tourist attraction is still limited and ineffective, this study aims to see how the implementation of promotion through digital media is used by the management and Koto Ruang Village, in addition to aiming to find out what obstacles are faced by the management. This study uses a qualitative descriptive method with data collection techniques through interviews, observations, and literature studies and documentation using key informants and supporters as sources of data information. The results of this study indicate that the implementation of digital promotion at the King Rokan Palace Cultural Heritage tourist attraction still has a lot to be fixed, especially in the field of increasing views through social media such as Facebook and Instagram. This is evidenced by the implementation of digital promotion that does not run as it should in the management of the tourist attraction. In addition, the management must increase the participation of the local community and youth. Keywords: Raja Rokan Palace, Digital Promotion, Rokan IV Koto District